Hearing Response Following Internal Auditory Canal Decompression in Neurofibromatosis Type 2. Issue 3 (September 2019) - Bonne, Nicolas‐Xavier; Risoud, Michaël; Hoa, Michael; Lemesre, Pierre‐Emmanuel; Aboukais, Rabih; Le Rhun, Emilie; Dubrulle, Frédérique; Baroncini, Marc; Lejeune, Jean‐Paul; Vincent, Christophe
Abstract : BACKGROUND: : Hearing response following an osteodural decompression of the internal auditory canal (IAC) is controversial. OBJECTIVE: : To evaluate the course of auditory brainstem responses (ABRs) and the early hearing response during the first year following IAC decompression for small to medium‐sized vestibular schwannomas occurring in neurofibromatosis type 2 (NF2). METHODS: : Retrospective chart review of middle fossa craniotomy for IAC osteodural decompression in NF2‐related vestibular schwannomas. RESULTS: : Twelve NF2 patients were operated on from 2011 to 2016 for IAC decompression. All had NF2 according to the Manchester criteria. All had a progressive change of their ABRs documented from the diagnosis of NF2 over a mean period of 6.25 [0.36;10.9] yr. Treatment was proposed to stop hearing progression based on the speech discrimination scores (SDSs; n = 4) or for hearing maintenance (n = 8). In patients with prior hearing progression, hearing responses were observed in 3 of the 4 patients during the first year. One patient kept on progressing. In the hearing maintenance group, the SDSs remained stable. SDSs improved from 85% [20–100] to 92.5% [60–100] on average (n = 12) and from 55% [20–80] to 77.5% [50–100] in the hearing progression group (n = 4). ABRs improved in 4 patients following decompression. CONCLUSION: : IAC decompression allows early objective hearing responses in select patients. We suggest that the procedure should be offered to patients with hearing progression based on their SDSs and/or associated progressive increases in their wave III and V latencies on ABRs.